2015
DOI: 10.3109/02713683.2015.1056378
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Synaptic Patterns of NMDA Receptor Subtypes Upon Direction-Selective Rabbit Retinal Ganglion Cells

Abstract: Our results indicate that direction selectivity appears to lie in the neuronal circuitry afferent to the DS RGCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…We previously reported that most glutamate receptors, including N-methyl- d -aspartate (NMDA), α-amino-3-hydroxy-5-methyl-4-isoxazole propionate (AMPA), and kainate (KA) receptors, showed no anatomical evidence of asymmetry in their distribution patterns on the dendrites of the ON-OFF DS RGCs in the adult rabbit retina [ 26 , 30 , 31 ]. Taken together, our previous and present expressional pattern results indicate that the excitatory neurotransmitters receptor subunits have no critical effect on the anisotropy of the ON-OFF DS RGCs for the induction of direction selectivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that most glutamate receptors, including N-methyl- d -aspartate (NMDA), α-amino-3-hydroxy-5-methyl-4-isoxazole propionate (AMPA), and kainate (KA) receptors, showed no anatomical evidence of asymmetry in their distribution patterns on the dendrites of the ON-OFF DS RGCs in the adult rabbit retina [ 26 , 30 , 31 ]. Taken together, our previous and present expressional pattern results indicate that the excitatory neurotransmitters receptor subunits have no critical effect on the anisotropy of the ON-OFF DS RGCs for the induction of direction selectivity.…”
Section: Discussionmentioning
confidence: 99%
“…These cells have bistratified dendrites at a depth of 20% and 70% of the inner plexiform layer (IPL) of the retina in sublamina a (OFF) and sublamina b (ON), respectively [ 7 , 11 , 13 , 29 , 49 , 50 , 57 ]. With their distinctive anatomical structures, various receptors are expressed in the ON-OFF DS RGCs [ 26 , 28 , 30 , 31 , 44 ], but the molecular profiles of the ON-OFF DS RGCs are not fully understood.…”
Section: Introductionmentioning
confidence: 99%